Discourage one to encourage another? Deleveraging and accounting conservatism - Shangkun Liang; Wen Wen; Nan Lin (China Journal of Accounting Studies (CJAS), 2024)
Deleveraging policies help mitigate firms' financial risks and reduce systemic economic risks, yet their other consequences need examination. Using data of A-share listed firms in China from 2012 to 2018, we find that after the implementing of the deleveraging policy, the accounting conservatism of firms facing a greater impact of the deleveraging policy significantly decreases. The impact mainly comes from long-term and bank loan leverage reduction, and from high initial leverage firms. The mechanism tests indicate that a deleveraging policy reduces accounting conservatism by mitigating a firm's default risk and weakening agency conflict between creditors and shareholders. Further analyses show that the impact of the deleveraging policy on accounting conservatism is more pronounced among firms with stronger policy implementation, firms in regions with low non-performing loans (NPL), firms without political connections, and non-zombie firms.
Keywords: 650; Accounting conservatism; Deleveraging Policy; initial leverage; term of leverage